Sports, physical activity and patient-reported outcomes after medial unicompartmental knee arthroplasty in young patients - Walker, Tilman; Streit, Julia; Gotterbarm, Tobias; Bruckner, Thomas; Merle, Christian; Streit, Marcus R. (The journal of arthroplasty, 2015)
One hundred-and-one patients age 60 or younger following medial mobile bearing UKA were reviewed retrospectively with a minimum follow-up of 2years using the Schulthess activity score, Tegner, UCLA and SF-36 score to assess their level of physical activity and quality of life. Patients showed a rapid recovery and resumption of their activities with a return-to-activity rate of 93%. Most common activities were low impact, whereas high-impact activities showed a significant decrease. Precaution was found to be the main reason for a decrease in the level of activity. The results of this study demonstrate that patients age 60 or younger following medial UKA were able to return to regular physical activities with almost two-thirds of the patients reaching a high activity level (UCLA≥7).
Gesehen am 26.06.2020